Graphene oxide prepared from failed lithium ion battery graphite and application method
Graphene oxide is prepared through high-temperature heat treatment, combined leaching of acid solutions and oxidants, improved Hummers method, and applied to concrete materials, solving the problems existing in the regeneration of graphite materials for failed lithium-ion batteries, and achieving efficient resource recycling and environmental protection.
Patent Information
- Application Number
- CN202510153854.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-25
AI Technical Summary
The graphite materials of failed lithium-ion batteries have problems such as poor selectivity, low adsorption performance, long process flow, low utilization rate and major secondary pollution during the regeneration process, resulting in waste of resources and environmental pollution.
Graphene oxide is prepared by high-temperature heat treatment, combined leaching of acid solutions and oxidants, and improved Hummers method, and applied it to concrete materials to improve its compressive resistance.
It effectively reduces the metal ion content and ash percentage in graphite, improves the compressive strength of graphene oxide, realizes the recycling and utilization of secondary resources, and reduces environmental pollution.
Smart Images

Figure CN119873812A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste treatment in the battery industry, and in particular to a method for preparing graphene oxide from failed lithium-ion battery graphite and an application method thereof. Background Art
[0002] During the production and preparation of lithium-ion batteries, graphite is the most commonly used negative electrode material. As the number of times lithium-ion batteries are charged and discharged increases, their capacity gradually decreases until they fail completely. Generally speaking, the life of lithium-ion batteries is 3 to 8 years, and they are scrapped after thousands of cycles. According to the latest statistics, it is estimated that by the end of 2025, the annual scrap volume of failed lithium-ion batteries will be 640,000 tons. The increasing number of retired lithium batteries has caused serious environmental pollution and waste of resources.
[0003] Previous studies have shown that: on the one hand, failed lithium-ion battery negative electrode graphite can be regenerated into products such as adsorbents, catalysts, supercapacitors and secondary electrode materials. The regenerated products have problems such as poor selectivity for metal ions, low adsorption performance, long process flow, low utilization rate and large secondary pollution, which can realize the closed-loop circulation of graphite materials. Therefore, based on the above regeneration method drawbacks, a method for preparing graphene oxide from failed lithium-ion battery graphite and its application is proposed. Summary of the invention
[0004] In view of this, the embodiments of the present invention hope to provide a method for preparing graphene oxide from failed lithium-ion battery graphite and its application, so as to solve or alleviate the technical problems existing in the prior art and at least provide a beneficial option.
[0005] The technical solution of the embodiment of the present invention is implemented as follows: a method for preparing graphene oxide from spent lithium-ion battery graphite comprises the following steps:
[0006] S1. The negative electrode graphite of the failed lithium-ion battery is subjected to high temperature heat treatment and then cooled to room temperature to obtain a negative electrode graphite calcined material;
[0007] S2, leaching the roasted slag obtained in S1 by using an acid solution and an oxidant, ultrasonic treatment is performed during the leaching process, and then filtering and separating to obtain a leachate and a leached slag;
[0008] S3, washing the leached residue obtained in S2 with water and then drying it to obtain regenerated graphite;
[0009] S4, using the regenerated graphite obtained in S3, preparing graphene oxide by adding an intercalating agent, an oxidant and hydrogen peroxide using an improved Hummers method, the whole process requires stirring, and the leached residue is washed and dried to obtain a graphene oxide material;
[0010] S5. Add the graphene oxide obtained in S4 into the dispersion for ultrasonic dispersion, and then add it to cement, sand, gravel, water and admixtures to form a graphene oxide-concrete material.
[0011] In some embodiments, the metal ion content of the graphite after the water washing treatment in S2 is 0.1-2.0 wt.%, and the ash weight percentage is 1.0-5.0 wt.%.
[0012] In some embodiments, the heating rate of the high temperature heat treatment in S1 is 2-10° C. / min, the heating temperature is 400-600° C., and the heating time is 0.5-4 h.
[0013] In some embodiments, the acidic solution in S2 is hydrochloric acid, the concentration of hydrochloric acid is 1.0-6.0 mol / L, the liquid-solid ratio is 3:1-10:1 mL / g, the temperature is 50-80° C., and the acid leaching time is 0.5-6.0 h.
[0014] In some embodiments, the oxidant in S2 is a hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 0.5-5.0 wt.%, the ultrasonic wave works in a continuous or indirect manner, and the working time is 0.5-6 hours.
[0015] In some embodiments, the intercalating agents in S4 are concentrated sulfuric acid and concentrated phosphoric acid, the volume and liquid-to-solid ratio of concentrated sulfuric acid and concentrated phosphoric acid to graphite is 5:1-20:1 mL / g, the molar ratio of concentrated sulfuric acid to concentrated phosphoric acid is 5:1-0.5:1, the stirring time at low temperature is 1-4 h, the temperature is 0-5°C, the stirring speed is 100-300 rpm, the stirring time in the medium temperature section is 1-4 h, the temperature is 25-50°C, the stirring speed is 100-300 rpm, the stirring time in the high temperature section is 0.5-2 h, the temperature is 60-90°C, and the stirring speed is 100-300 rpm.
[0016] In some embodiments, the oxidant in S4 is potassium permanganate, the mass ratio of potassium permanganate to graphite is 2 to 5:1, the mass fraction of the hydrogen peroxide solution is 0.5 to 5.0 wt.%, the stirring time at low temperature is 1 to 4 hours, the temperature is 0 to 5°C, the stirring speed is 100 to 300 rpm, the stirring time in the medium temperature section is 1 to 4 hours, the temperature is 25 to 50°C, the stirring speed is 100 to 300 rpm, the stirring time in the high temperature section is 0.5 to 2 hours, the temperature is 60 to 90°C, and the stirring speed is 100 to 300 rpm.
[0017] In some embodiments, the liquid-to-solid ratio of the graphene oxide and the dispersion in S5 is 1:10 to 1:50 mL / g, the ultrasonic working mode is continuous or indirect, the ultrasonic time is 0.2 to 0.5 h, and the ultrasonic frequency is 20 to 60 kHz.
[0018] In some embodiments, in S5, the proportion of graphene oxide in cement is 0.02wt.% to 0.07wt.%, the mass ratio of cement, sand, gravel, water and admixture is 154-362:626-771:1065-1066:160-182:7.4-14.7, and the compressive strength of graphene oxide-concrete material is increased by 7% to 10%.
[0019] A method for preparing graphene oxide from failed lithium-ion battery graphite and its application in concrete materials.
[0020] The embodiment of the present invention has the following advantages due to the adoption of the above technical solution:
[0021] The present invention prepares graphene oxide and applies it to concrete materials through high-temperature calcination, hydrochloric acid combined with hydrogen peroxide leaching, and improved Hummers method, so that the ion concentration of graphite can be reduced to ppm level, the metal Fe content can be reduced to below 50ppm, and the weight percentage of ash is less than 0.1%. The low-layer graphene oxide material is prepared by the improved Hummers method and applied to the construction industry such as concrete, so that its compressive resistance is improved, and finally the recovery and utilization of secondary resources are realized.
[0022] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 XRD patterns of waste graphite and purified graphite of the present invention;
[0025] Figure 2 The SEM images of purified graphite (a, b, c) and graphene oxide (d, e, f) of the present invention are shown;
[0026] Figure 3 Transmission electron microscopy images of purified graphite (a, b) and graphene oxide (c, d) of the present invention. DETAILED DESCRIPTION
[0027] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.
[0028] It should be noted that the terms "first", "second", "symmetrical", "array", etc. are only used to distinguish between description and position description purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the definition of "first", "symmetrical", etc. can explicitly or implicitly include one or more of these features; similarly, when the quantity of certain features is not limited in the form of words such as "two" or "three", it should be noted that this feature also explicitly or implicitly includes one or more feature quantities;
[0029] In the present invention, unless otherwise clearly specified and limited, the terms such as "installation", "connection", "fixation" and the like should be understood in a broad sense; for example, it can be a fixed connection, a detachable connection, or an integral molding; it can be a mechanical connection, a direct connection, welding, or an indirect connection through an intermediate medium, or it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood based on the description and drawings combined with specific circumstances.
[0030] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0031] Embodiment 1
[0032] like Figure 1-Figure 3 As shown, an embodiment of the present invention provides a method for preparing graphene oxide from spent lithium-ion battery graphite, comprising the following steps:
[0033] S1. 10 g of failed lithium-ion battery negative electrode graphite (carbon content of 97.2%, Na content of 0.16wt.%, Cu content of 0.25wt.%, Al content of 0.04wt.%, Co content of 0.04wt.%, Fe content of 0.36wt.%) was subjected to high temperature heat treatment and then cooled to room temperature to obtain negative electrode graphite calcined material;
[0034] S2, leaching the roasted slag obtained in S1 by using an acid solution and an oxidant, ultrasonic treatment is performed during the leaching process, and then filtering and separating to obtain a leachate and a leached slag (carbon content is 99.6wt.%, Na content is 0.01wt.%, Cu content is 0.01wt.%, Al content is 0.01wt.%, Co content is 0, and Fe content is 0.01wt.%);
[0035] S3, washing the leached residue obtained in S2 with water and then drying it to obtain regenerated graphite;
[0036] S4, using the regenerated graphite obtained in S3, preparing graphene oxide by adding an intercalating agent, an oxidant and hydrogen peroxide using an improved Hummers method, the whole process requires stirring, and the leached residue is washed and dried to obtain a graphene material with a small number of oxidized layers (n=15);
[0037] S5. Add the graphene oxide obtained in S4 into the dispersion for ultrasonic dispersion, and then add it to cement, sand, gravel, water and admixtures to form a graphene oxide-concrete material.
[0038] In this embodiment, specifically, the metal ion content of the graphite after the water washing treatment in S2 is 0.1-2.0 wt.%, and the ash weight percentage is 1.0-5.0 wt.%.
[0039] In this embodiment, specifically, the heating rate of the high temperature heat treatment in S1 is 2-10° C. / min, the heating temperature is 500° C., and the heating time is 40 min.
[0040] In this embodiment, specifically, the acidic solution in S2 is hydrochloric acid, the hydrochloric acid concentration is 4.0 mol / L, the liquid-solid ratio is 7.5:1 mL / g, the temperature is 80° C., and the acid leaching time is 4.0 h.
[0041] In this embodiment, specifically, the oxidant in S2 is a hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 5.0 wt.%, the ultrasonic wave works in a continuous or indirect manner, and the working time is 0.5 to 6 hours.
[0042] In this embodiment, specifically, the intercalating agents in S4 are concentrated sulfuric acid and concentrated phosphoric acid, the volume and liquid-solid ratio of concentrated sulfuric acid and concentrated phosphoric acid to graphite is 20:1 mL / g, the molar ratio of concentrated sulfuric acid to concentrated phosphoric acid is 3:1, the concentration of concentrated sulfuric acid is 18.0 mol / L, the concentration of concentrated phosphoric acid is 19.0 mol / L, the stirring time at low temperature is 1 to 4 h, the temperature is 0 to 5 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the medium temperature section is 1 to 4 h, the temperature is 25 to 50 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the high temperature section is 0.5 to 2 h, the temperature is 60 to 90 ° C, and the stirring speed is 100 to 300 rpm.
[0043] In this embodiment, specifically, the oxidant in S4 is potassium permanganate, the mass ratio of potassium permanganate to graphite is 2:1, the mass fraction of the hydrogen peroxide solution is 0.2wt.%, the stirring time at low temperature is 1 to 4 hours, the temperature is 0 to 5°C, the stirring speed is 100 to 300rpm, the stirring time in the medium temperature section is 1 to 4 hours, the temperature is 25 to 50°C, the stirring speed is 100 to 300rpm, the stirring time in the high temperature section is 0.5 to 2 hours, the temperature is 60 to 90°C, and the stirring speed is 100 to 300rpm.
[0044] In this embodiment, specifically, the liquid-to-solid ratio of the graphene oxide and the dispersion in S5 is 1:50 mL / g, the ultrasonic working mode is continuous or indirect, the ultrasonic time is 0.2 to 0.5 h, and the ultrasonic frequency is 20 to 60 kHz.
[0045] In this embodiment, specifically, in S5, the proportion of graphene oxide in cement is 0.065wt.%, the mass ratio of cement, sand, gravel, water and admixture is 154:771:1065:182:7.4, and the compressive strength of graphene oxide-concrete material is increased from 20Mpa to 21.7Mpa, and the performance is improved by 8.4%.
[0046] A method for preparing graphene oxide from failed lithium-ion battery graphite and its application in concrete materials.
[0047] Embodiment 2
[0048] like Figure 1-Figure 3 As shown, an embodiment of the present invention provides a method for preparing graphene oxide from spent lithium-ion battery graphite, comprising the following steps:
[0049] S1. 10 g of failed lithium-ion battery negative electrode graphite (carbon content of 97.6%, Na content of 0.13wt.%, Cu content of 0.21wt.%, Al content of 0.04wt.%, Fe content of 0.32wt.%) was subjected to high temperature heat treatment and then cooled to room temperature to obtain a negative electrode graphite calcined material;
[0050] S2, leaching the roasted slag obtained in S1 by using an acid solution and an oxidant, performing ultrasonic treatment during the leaching process, and then filtering and separating to obtain a leachate and a leached slag (with a carbon content of 99.6wt.%, a Na content of 0.01wt.%, a Cu content of 0.01wt.%, an Al content of 0.01wt.%, a Co content of 0, and a Fe content of 0.02wt.%);
[0051] S3, washing the leached residue obtained in S2 with water and then drying it to obtain regenerated graphite;
[0052] S4, using the regenerated graphite obtained in S3, preparing graphene oxide by adding an intercalating agent, an oxidant and hydrogen peroxide using an improved Hummers method, the whole process requires stirring, and the leached residue is washed and dried to obtain a graphene material with a small number of oxidized layers (n=13);
[0053] S5. Add the graphene oxide obtained in S4 into the dispersion for ultrasonic dispersion, and then add it to cement, sand, gravel, water and admixtures to form a graphene oxide-concrete material.
[0054] In this embodiment, specifically, the metal ion content of the graphite after the water washing treatment in S2 is 0.1-2.0 wt.%, and the ash weight percentage is 1.0-5.0 wt.%.
[0055] In this embodiment, specifically, the heating rate of the high temperature heat treatment in S1 is 2-10° C. / min, the heating temperature is 500° C., and the heating time is 40 min.
[0056] In this embodiment, specifically, the acidic solution in S2 is hydrochloric acid, the hydrochloric acid concentration is 6.0 mol / L, the liquid-solid ratio is 7.5:1 mL / g, the temperature is 70° C., and the acid leaching time is 5.0 h.
[0057] In this embodiment, specifically, the oxidant in S2 is a hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 3.0 wt.%, the ultrasonic wave works in a continuous or indirect manner, and the working time is 0.5 to 6 hours.
[0058] In this embodiment, specifically, the intercalating agents in S4 are concentrated sulfuric acid and concentrated phosphoric acid, the volume and liquid-solid ratio of concentrated sulfuric acid and concentrated phosphoric acid to graphite is 15:1 mL / g, the molar ratio of concentrated sulfuric acid to concentrated phosphoric acid is 3:1, the concentration of concentrated sulfuric acid is 15.0 mol / L, the concentration of concentrated phosphoric acid is 15.5 mol / L, the stirring time at low temperature is 1 to 4 h, the temperature is 0 to 5 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the medium temperature section is 1 to 4 h, the temperature is 25 to 50 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the high temperature section is 0.5 to 2 h, the temperature is 60 to 90 ° C, and the stirring speed is 100 to 300 rpm.
[0059] In this embodiment, specifically, the oxidant in S4 is potassium permanganate, the mass ratio of potassium permanganate to graphite is 2:1, the mass fraction of the hydrogen peroxide solution is 0.25wt.%, the stirring time at low temperature is 1 to 4 hours, the temperature is 0 to 5°C, the stirring speed is 100 to 300rpm, the stirring time in the medium temperature section is 1 to 4 hours, the temperature is 25 to 50°C, the stirring speed is 100 to 300rpm, the stirring time in the high temperature section is 0.5 to 2 hours, the temperature is 60 to 90°C, and the stirring speed is 100 to 300rpm.
[0060] In this embodiment, specifically, the liquid-to-solid ratio of the graphene oxide and the dispersion in S5 is 1:50 mL / g, the ultrasonic working mode is continuous or indirect, the ultrasonic time is 0.2 to 0.5 h, and the ultrasonic frequency is 20 to 60 kHz.
[0061] In this embodiment, specifically, in S5, the proportion of graphene oxide in cement is 0.049wt.%, the mass ratio of cement, sand, gravel, water and admixture is 206:722:1083:168:9.4, and the compressive strength of graphene oxide-concrete material is increased from 30Mpa to 32.6Mpa, and the performance is improved by 8.6%.
[0062] A method for preparing graphene oxide from failed lithium-ion battery graphite and its application in concrete materials.
[0063] Embodiment 3
[0064] like Figure 1-Figure 3 As shown, an embodiment of the present invention provides a method for preparing graphene oxide from spent lithium-ion battery graphite, comprising the following steps:
[0065] S1. 10 g of failed lithium-ion battery negative electrode graphite (carbon content of 98.1%, Na content of 0.10 wt.%, Cu content of 0.17 wt.%, Al content of 0.03 wt.%, Fe content of 0.25 wt.%) was subjected to high temperature heat treatment and then cooled to room temperature to obtain a negative electrode graphite calcined material;
[0066] S2, leaching the roasted slag obtained in S1 by using an acid solution and an oxidant, performing ultrasonic treatment during the leaching process, and then filtering and separating to obtain a leachate and a leached slag (carbon content is 99.6wt.%, Na content is 0wt.%, Cu content is 0.02wt.%, Al content is 0.01wt.%, Co content is 0, and Fe content is 0.01wt.%);
[0067] S3, washing the leached residue obtained in S2 with water and then drying it to obtain regenerated graphite;
[0068] S4, using the regenerated graphite obtained in S3, preparing graphene oxide by adding an intercalating agent, an oxidant and hydrogen peroxide using an improved Hummers method, the whole process requires stirring treatment, and the leached residue is washed and dried to obtain a graphene material with a small number of oxidized layers (n=17);
[0069] S5. Add the graphene oxide obtained in S4 into the dispersion for ultrasonic dispersion, and then add it to cement, sand, gravel, water and admixtures to form a graphene oxide-concrete material.
[0070] In this embodiment, specifically, the metal ion content of the graphite after the water washing treatment in S2 is 0.1-2.0 wt.%, and the ash weight percentage is 1.0-5.0 wt.%.
[0071] In this embodiment, specifically, the heating rate of the high temperature heat treatment in S1 is 2-10° C. / min, the heating temperature is 500° C., and the heating time is 40 min.
[0072] In this embodiment, specifically, the acidic solution in S2 is hydrochloric acid, the hydrochloric acid concentration is 4.0 mol / L, the liquid-solid ratio is 10:1 mL / g, the temperature is 80° C., and the acid leaching time is 5.0 h.
[0073] In this embodiment, specifically, the oxidant in S2 is a hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 5.0 wt.%, the ultrasonic wave works in a continuous or indirect manner, and the working time is 0.5 to 6 hours.
[0074] In this embodiment, specifically, the intercalating agents in S4 are concentrated sulfuric acid and concentrated phosphoric acid, the volume and liquid-solid ratio of concentrated sulfuric acid and concentrated phosphoric acid to graphite is 30:1 mL / g, the molar ratio of concentrated sulfuric acid to concentrated phosphoric acid is 3:1, the concentration of concentrated sulfuric acid is 12.0 mol / L, the concentration of concentrated phosphoric acid is 11.7 mol / L, the stirring time at low temperature is 1 to 4 h, the temperature is 0 to 5 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the medium temperature section is 1 to 4 h, the temperature is 25 to 50 ° C, the stirring speed is 100 to 300 rpm, the stirring time in the high temperature section is 0.5 to 2 h, the temperature is 60 to 90 ° C, and the stirring speed is 100 to 300 rpm.
[0075] In this embodiment, specifically, the oxidant in S4 is potassium permanganate, the mass ratio of potassium permanganate to graphite is 2.5:1, the mass fraction of the hydrogen peroxide solution is 0.50wt.%, the stirring time at low temperature is 1 to 4 hours, the temperature is 0 to 5°C, the stirring speed is 100 to 300rpm, the stirring time in the medium temperature section is 1 to 4 hours, the temperature is 25 to 50°C, the stirring speed is 100 to 300rpm, the stirring time in the high temperature section is 0.5 to 2 hours, the temperature is 60 to 90°C, and the stirring speed is 100 to 300rpm.
[0076] In this embodiment, specifically, the liquid-to-solid ratio of the graphene oxide and the dispersion in S5 is 1:50 mL / g, the ultrasonic working mode is continuous or indirect, the ultrasonic time is 0.2 to 0.5 h, and the ultrasonic frequency is 20 to 60 kHz.
[0077] In this embodiment, specifically, in S5, the proportion of graphene oxide in cement is 0.028wt.%, the mass ratio of cement, sand, gravel, water and admixture is 362:626:1066:160:14.7, and the compressive strength of graphene oxide-concrete material is increased from 50Mpa to 54.5Mpa, and the performance is improved by 8.9%.
[0078] A method for preparing graphene oxide from failed lithium-ion battery graphite and its application in concrete materials.
[0079] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of various changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing graphene oxide from spent lithium-ion battery graphite, characterized in that: The following steps are involved: S1. The negative electrode graphite of the failed lithium-ion battery is subjected to high temperature heat treatment and then cooled to room temperature to obtain a negative electrode graphite calcined material; S2, leaching the roasted slag obtained in S1 by using an acid solution and an oxidant, ultrasonic treatment is performed during the leaching process, and then filtering and separating to obtain a leachate and a leached slag; S3, washing the leached residue obtained in S2 with water and then drying it to obtain regenerated graphite; S4, using the regenerated graphite obtained in S3, preparing graphene oxide by adding an intercalating agent, an oxidant and hydrogen peroxide using an improved Hummers method, the whole process requires stirring, and the leached residue is washed and dried to obtain a graphene oxide material; S5. Add the graphene oxide obtained in S4 into the dispersion for ultrasonic dispersion, and then add it to cement, sand, gravel, water and admixtures to form a graphene oxide-concrete material.
2. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, wherein: The heating rate of the high temperature heat treatment in S1 is 2-10°C / min, the heating temperature is 400-600°C, and the heating time is 0.5-4h.
3. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, wherein: The acid solution in S2 is hydrochloric acid, the concentration of hydrochloric acid is 1.0-6.0 mol / L, the liquid-solid ratio is 3:1-10:1 mL / g, the temperature is 50-80°C, and the acid leaching time is 0.5-6.0 h.
4. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, wherein: The oxidant in S2 is hydrogen peroxide solution, the mass fraction of the hydrogen peroxide solution is 0.5-5.0wt.%, the ultrasonic wave works in a continuous or indirect manner, and the working time is 0.5-6h.
5. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, wherein: The intercalating agents in S4 are concentrated sulfuric acid and concentrated phosphoric acid, the volume and liquid-to-solid ratio of concentrated sulfuric acid and concentrated phosphoric acid to graphite is 5:1-20:1 mL / g, the molar ratio of concentrated sulfuric acid to concentrated phosphoric acid is 5:1-0.5:1, the stirring time at low temperature is 1-4 h, the temperature is 0-5°C, the stirring speed is 100-300 rpm, the stirring time in the medium temperature section is 1-4 h, the temperature is 25-50°C, the stirring speed is 100-300 rpm, the stirring time in the high temperature section is 0.5-2 h, the temperature is 60-90°C, and the stirring speed is 100-300 rpm.
6. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, characterized in that: The oxidant in S4 is potassium permanganate, the mass ratio of potassium permanganate to graphite is 2-5:1, the mass fraction of hydrogen peroxide solution is 0.5-5.0wt.%, the stirring time at low temperature is 1-4h, the temperature is 0-5°C, the stirring speed is 100-300rpm, the stirring time in the medium temperature section is 1-4h, the temperature is 25-50°C, the stirring speed is 100-300rpm, the stirring time in the high temperature section is 0.5-2h, the temperature is 60-90°C, and the stirring speed is 100-300rpm.
7. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, characterized in that: The liquid-to-solid ratio of the graphene oxide and the dispersion in the S5 is 1:10-1:50 mL / g, the ultrasonic working mode is continuous or indirect, the ultrasonic time is 0.2-0.5 h, and the ultrasonic frequency is 20-60 kHz.
8. The method for preparing graphene oxide from spent lithium-ion battery graphite according to claim 1, characterized in that: In the S5, the proportion of graphene oxide in cement is 0.02wt.% to 0.07wt.%, and the mass ratio of cement, sand, gravel, water and admixture is 154-362:626-771:1065-1066:160-182:7.4-14.
7.
9. Use of graphene oxide prepared from spent lithium-ion battery graphite according to claim 1 to claim 8 in concrete materials.
Citation Information
Patent Citations
Graphene cement-based intelligent concrete material and preparation method thereof
CN105801047A
Method for preparing porous graphene by recycling graphite cathode materials from waste power batteries
CN110589812A
High-valued recovery method of lithium battery graphite negative electrode waste
CN114843650A
Recycling method of lithium ion battery negative electrode graphite, graphite and battery
CN117735543A
Method for preparing battery-grade graphite by taking mixed waste of positive and negative electrode materials of invalid lithium ion battery as raw material
CN119234346A